Intraspecific variation in ultrastructure and secretion of the resin canals in Anacardium humile (Anacardiaceae) - de Carvalho, Shelly Favorito [UNESP]; Scudeler, Elton Luiz [UNESP]; dos Santos, Daniela Carvalho [UNESP]; Machado, Silvia Rodrigues [UNESP] (Springer Nature, 2023)
The study combines a range of light and electron microscopy methods to access variation in secretion and ultrastructure in the secretory canals in the above- and belowground stems of Anacardium humile, which here serves as a model system. The aboveground stem canals show epithelial cells with ultrastructural characteristics typical of cells active in secretion, while in the belowground stems, the subcellular characteristics are typical of cells with low rates of metabolism. The secretory canals of the belowground stems show uniformity in size and shape, a large central vacuole, a cytoplasm reduced to a thin layer at the cell periphery, and a reduced population of organelles. The aboveground stem canals had voluminous nuclei with evident nucleoli, a very dense cytoplasm with free ribosomes, polyribosomes, mitochondria with developed cristae, and ellipsoid plastids with electron-opaque droplets surrounded by a periplastid reticulum. The vacuoles were of different sizes and often had membranous contents and the dictyosomes were very developed with dilated ends to the cisternae, rough endoplasmic reticulum, and numerous vesicles. The results show that particularities in above- and belowground environment have significant implications for ultrastructural morphology and functioning of secretory canals in the stems of A. humile.
Keywords: Anacardiaceae; Cytology; Histochemistry; Secretory canals; Ultrastructural cytochemistry